Pregunta
upstudy study bank question image url

\( 3 x+4 y=-24 \) and \( 7 x-4 y=-16 \)

Ask by Carlson Guzman. in South Africa
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( x=-4 \) and \( y=-3 \).

Solución

Solve the system of equations \( 3x+4y=-24;7x-4y=-16 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+4y=-24\\7x-4y=-16\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-\frac{24+4y}{3}\\7x-4y=-16\end{array}\right.\) - step2: Substitute the value of \(x:\) \(7\left(-\frac{24+4y}{3}\right)-4y=-16\) - step3: Multiply the terms: \(-\frac{7\left(24+4y\right)}{3}-4y=-16\) - step4: Multiply both sides of the equation by LCD: \(\left(-\frac{7\left(24+4y\right)}{3}-4y\right)\times 3=-16\times 3\) - step5: Simplify the equation: \(-168-40y=-48\) - step6: Move the constant to the right side: \(-40y=-48+168\) - step7: Add the numbers: \(-40y=120\) - step8: Change the signs: \(40y=-120\) - step9: Divide both sides: \(\frac{40y}{40}=\frac{-120}{40}\) - step10: Divide the numbers: \(y=-3\) - step11: Substitute the value of \(y:\) \(x=-\frac{24+4\left(-3\right)}{3}\) - step12: Substitute back: \(x=\frac{-24+4\times 3}{3}\) - step13: Calculate: \(x=-4\) - step14: Calculate: \(\left\{ \begin{array}{l}x=-4\\y=-3\end{array}\right.\) - step15: Check the solution: \(\left\{ \begin{array}{l}x=-4\\y=-3\end{array}\right.\) - step16: Rewrite: \(\left(x,y\right) = \left(-4,-3\right)\) The solution to the system of equations \(3x+4y=-24\) and \(7x-4y=-16\) is \(x=-4\) and \(y=-3\).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the system of equations, you can use the method of elimination or substitution. If you choose elimination, you can add the two equations directly: 1. \( 3x + 4y = -24 \) 2. \( 7x - 4y = -16 \) Adding these gives you \( 10x = -40 \), so \( x = -4 \). Next, plug \( x = -4 \) back into either equation to find \( y \): Using the first equation: \( 3(-4) + 4y = -24 \) leads to \( -12 + 4y = -24 \), thus \( 4y = -12 \) and \( y = -3 \). So the solution is \( x = -4 \) and \( y = -3 \). Solving systems of equations might seem daunting, but it’s like a puzzle! It’s all about finding where the lines (or equations) intersect. No secret detective skills necessary—just a bit of number crunching! Making a common mistake involves misreading signs when adding or subtracting equations. Always double-check if you're applying the right operation! Mistakes like these can lead to incorrect solutions. So, when in doubt, check every step to ensure your calculations are spot on!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad